2017
DOI: 10.2147/ndt.s129522
|View full text |Cite
|
Sign up to set email alerts
|

Compound porcine cerebroside and ganglioside injection attenuates cerebral ischemia–reperfusion injury in rats by targeting multiple cellular processes

Abstract: BackgroundCompound porcine cerebroside and ganglioside injection (CPCGI) is a neurotrophic drug used clinically to treat certain functional disorders of brain. Despite its extensive usage throughout China, the exact mechanistic targets of CPCGI are unknown. This study was carried out to investigate the protective effect of CPCGI against ischemic neuronal damage in rats with middle cerebral artery occlusion (MCAO) reperfusion injury and to investigate the neuroprotective mechanisms of CPCGI.Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…CPCGI, which is a potent treatment for many diseases, is involved in reducing cell apoptosis and enhancing synaptic functions. Previous studies have reported that CPCGI promotes neurogenesis by mediating cell apoptosis in hippocampal neurons, and its neuroprotective effects in MCAO-induced injury models have also been documented [6]. However, whether CPCGI participates in the progression of sevoflurane-stimulated injury in hippocampal neuronal cells has been unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPCGI, which is a potent treatment for many diseases, is involved in reducing cell apoptosis and enhancing synaptic functions. Previous studies have reported that CPCGI promotes neurogenesis by mediating cell apoptosis in hippocampal neurons, and its neuroprotective effects in MCAO-induced injury models have also been documented [6]. However, whether CPCGI participates in the progression of sevoflurane-stimulated injury in hippocampal neuronal cells has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CPCGI (drug approval H22026472, China) has widespread clinical use for Alzheimer's disease, craniocerebral injury, spinal cord injury, and traumatic peripheral nerve injury therapy in China [6][7][8]. In addition, monosialotetrahexosyl ganglioside (GM-1) and hypoxanthine, the main components of CPCG, can promote the metabolism of brain tissue, are involved in neuron growth, differentiation, and regeneration, and accelerate the brain blood circulation [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In 2010, the China Food and Drug Administration approved compound porcine cerebroside and ganglioside injection (CPCGI), a neurotrophic drug, for use in the treatment of stroke, Alzheimer's disease, and central and peripheral nerve injuries. [10][11][12][13] The main components of CPCGI include polypeptides, various gangliosides, and hypoxanthine, etc. CPCGI has been reported to improve cerebral blood circulation and neurological function, reduce apoptotic cell death, and prompt the recovery of synaptic and mitochondrial function in a rat model of focal cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…CPCGI has been reported to improve cerebral blood circulation and neurological function, reduce apoptotic cell death, and prompt the recovery of synaptic and mitochondrial function in a rat model of focal cerebral ischemia. 10 , 13 However, there is no report about the protective effects of CPCGI against TBI. In the present study, we primarily investigated whether CPCGI protected the brain against TBI through upregulating Nrf2 signaling and suppressing calpain overactivation due to oxidative stress in a rat model of controlled cortical impact (CCI).…”
Section: Introductionmentioning
confidence: 99%